The Use of Slang Words in “The Black Panther” Movie - Dewa Ayu Febri Rantika; I Nengah Sudipa; I Nyoman Aryawibawa (Research and Community Services Institutes of Udayana University, 2023)
The title of this study is a slang word in the movie The Black Panther by Ryan Coogler. This study focuses on identifying the types of slang words and analyze the meaning of one's utterance by the characters in the movie. The data was taken from the movie entitled The Black Panther and were collected by using the observation method. The data were analyzed by using the qualitative method. The types of slang words were analyzed base on the theory proposed by Chapman (1988) who divided types of slang words into two types. The meaning of the slang word is analyzed based on the theory proposed by Leech (1981) who divided the meaning of slang word into 7 types. Based on the result of the analysis show that there are two types of slang words found in this study; primary slang and secondary slang. There are seven meanings of slang words found in this study; conceptual meaning, connotative meaning, affective meaning, social meaning, reflected meaning, collocative meaning and thematic meaning.